Study of oil transport in surf zone and turbulance generated by oscillating grid - Cheng, Nian Sheng. (Nanyang Technological University, 2008)
First part of the project, oil transport subjected to nearshore currents in the surf zone is considered using the mass conservation equation. second part presents an investigation of turbulance generated by a vertically oscillating grid in a water tank using the DPIV technique.